Selective Nonroutine Microbial Surveillance of In-Use Hospital Nebulizers by Aerosol Entrapment and Direct Sampling Analyses of Solutions in Reservoirs - Reinhardt, Donald J. (1980)
Effluent aerosols and liquid reservoir samples from 255 in-use hospital nebulization devices were analyzed by Aero-Test samplers (Olympic Corp.) and direct dilution procedures (0.1-, 0.01-, and 0.001-ml plated samples). Thirty-five percent (89 of 255) of the in-use hospital reservoir samples were positive by direct dilution, and 24% (61 of 255) were positive by Aero- Test samplers. Acinetobacter calcoaceticus var. anitratus was found either alone or in association with Pseudomonas spp. in 50% of all the contaminated in-use reservoirs. This indicates a high endemicity for Acinetobacter in the environment studied. Viable microbes in the reservoirs of contaminated nebulizers ranged from as few as 20 to >2 × 10(5) colony-forming units/ml. Microbial contamination at moderate to heavy levels (1 × 10(4) to >2 × 10(5)) was regularly detected by both procedures. Microbial densities of 10(3) colony-forming units/ml and less in contaminated reservoirs often were negative in the Aero- Test but positive by direct dilution techniques. These hospital-based results were similar to laboratory data obtained with sterile nebulizers intentionally contaminated in graduated densities with either Staphylococcus aureus or Pseudomonas aeruginosa. Sensitivity of the Aero- Test system was best when ≥10(4) colony-forming units/ml were present in the reservoirs of operating nebulizers. The manufacturer suggests that five or less colonies appearing after sampling on Aero- Test plates upon 48-h incubation does not indicate contamination of the reservoir. Our data show that even a single colony, particularly if it is typical, water-associated, gram-negative bacterial species, may well indicate low levels of reservoir contamination. Both the Aero- Test and direct dilution methods indicated the need for more rigorous management of the in-use respiratory therapy equipment in the hospital surveyed. These studies demonstrate the value of selective nonroutine surveillance for identifying potential or actual contamination problems of in-use nebulizing equipment, particularly when recommended care guidelines are not followed due to choice or unawareness. Ameliorative-corrective measures, which included routine 24-h substitution of old units with new sterile units, were initiated as a result of this surveillance program.